2021
DOI: 10.1371/journal.pone.0249565
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with unfavorable treatment outcomes in patients with rifampicin-resistant tuberculosis in Colombia 2013–2015: A retrospective cohort study

Abstract: Background Multidrug- and rifampicin (RMP)-resistant tuberculosis (MDR/RR-TB) requires prolonged and expensive treatment, which is difficult to sustain in the Colombian health system. This requires the joint action of different providers to provide timely health services to people with TB. Identifying factors associated with unfavorable treatment outcomes in patients with MDR/RR-TB who received drug therapy between 2013 and 2015 in Colombia can help guide the strengthening of the national TB control program. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In the present study, the prevalence of death rate was 21.7%; this figure was similar to reports from previous studies conducted in Colombia, India, and South Africa [30][31][32]. However, this was lower than the death rate reported in studies from Western India and Ukraine [25,26].…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the prevalence of death rate was 21.7%; this figure was similar to reports from previous studies conducted in Colombia, India, and South Africa [30][31][32]. However, this was lower than the death rate reported in studies from Western India and Ukraine [25,26].…”
Section: Discussionsupporting
confidence: 89%
“…Comparable to our study, Chaves-Torres NM et al . [ 32 ] study in Colombia found successful treatment in 49.9% MDR/RR-TB cohort. El Hamdouni et al .…”
Section: Discussionmentioning
confidence: 99%
“…The overall mortality was 30% and the mortality rate during the intensive phase was 23%; this frequency was similar to results from previous studies conducted in Pakistan and Colombia while lower from the India. 6,9,10 When death due to MDR-TB was considered, underweight was associated with an increased risk of mortality during MDR-TB treatment in our study. This association between underweight and the active tuberculosis has been thoroughly mentioned in scientific literature.…”
Section: Discussionmentioning
confidence: 57%